Doping effect on the physical properties of bi-layered aurivillius-type structure SrBi2Nb2O9 ferroelectric ceramics: SrBi2Nb2O9 (SBN) aurivillius-type ferroelectric ceramics - Reis, I. C.; Silva, A. C.; Guo, R.; Bhalla, A. S.; Guerra, J. D.S. (Institute of Electrical and Electronics Engineers (IEEE), 2014)
The doping effect on the structural, microstructural and dielectric properties of bismuth layer structured SrBi2Nb2O9(SBN) ferroelectric ceramics has been investigated. The samples were obtained from the solid state reaction sintering method. Particularly, the A-site cation substitution of Sr2+ by La3+ has been considered, taking into account the lanthanum concentration (x) up to 30 at.%. It has been found that the physical properties of the studied Sr1-3x/2LaxBi2Nb2O9(SLBN) system are strongly affected by the doping content. The characteristics of the phase transition were investigated from the dielectric response, performed in a wide temperature and frequency range.
Keywords: Aurivillius; ceramics; dielectric properties; ferroelectrics